2001
DOI: 10.1590/s0102-09352001000100001
|View full text |Cite
|
Sign up to set email alerts
|

Urbanização da leishmaniose visceral em Belo Horizonte

Abstract: O Brasil vivencia na atualidade uma situação na qual velhas endemias, que se pensava esquecidas, ressurgem com grande impacto e muitas vezes com perfis de morbi-mortalidades diferentes daqueles já conhecidos. Este é o caso da leishmaniose visceral, uma doença caracteristicamente rural e associada a condições precárias de vida, que encontra no espaço urbano ambiente favorável para se estabelecer e desenvolver. O município de Belo Horizonte convive, desde 1993, com uma epidemia de calazar humano e canino. Foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
32

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 6 publications
0
34
0
32
Order By: Relevance
“…The clinical diagnosis is complex and should be performed using a combination of serological, parasitological, and/or molecular tests (SILVA, 2007). According to a study conducted by Bevilacqua et al (2001), CVL precedes human cases because the spatial and chronological distribution of canine cases in the city of Belo Horizonte -MG has occurred much earlier than reports of human cases. Therefore, dogs are considered the main reservoir of the disease for humans.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis is complex and should be performed using a combination of serological, parasitological, and/or molecular tests (SILVA, 2007). According to a study conducted by Bevilacqua et al (2001), CVL precedes human cases because the spatial and chronological distribution of canine cases in the city of Belo Horizonte -MG has occurred much earlier than reports of human cases. Therefore, dogs are considered the main reservoir of the disease for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this metaxenic disease has been naturally transmitted in periurban areas due to the emergence and reemergence of its vectors in such areas (Tauil 2006). Recent data have confirmed urbanization of the disease in large urban centers (Silva et al 2001, Bevilacqua et al 2001, Souza et al 2004; add to this the fact that some investigators (Bevilacqua et al 2001) have suggested that socio-economical factors may be one of the determinant factors for VL transmission in Brazil.…”
mentioning
confidence: 92%
“…Nestes, o cão é considerado o principal reservatório doméstico, e estudos demonstram que altas taxas de prevalência canina estão associadas à ocorrência de casos humanos (Bevilacqua et al, 2001;Luz et al, 2001).…”
unclassified